2019
DOI: 10.1016/j.msec.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and biological properties of electrodeposited calcium phosphate coatings

Abstract: Calcium phosphate (CaeP) coatings were electrochemically deposited on titanium substrates. By increasing the electrodeposition time (from 1 to 30 min), the coating thickness increases but also the surface morphology of the CaeP coatings is greatly affected going from smooth to plate-like, featuring elongated plates, ribbon-like and finally sharp needle structures. Micro-stretch tests reveal that, regardless of the coating morphology and thickness, the electrodeposited CaeP coatings have strong adhesion with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…The smooth and homogeneous surface coatings clearly induced better cell adhesion, viability, and proliferation than rough surfaces. This behavior may be attributed to the larger contact surface area between the cells and the coating [ 20 , 65 ]. Kamitakahara et al [ 66 ] reported that the wide contact surface area is an important factor for cell proliferation and cells could proliferate easily.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smooth and homogeneous surface coatings clearly induced better cell adhesion, viability, and proliferation than rough surfaces. This behavior may be attributed to the larger contact surface area between the cells and the coating [ 20 , 65 ]. Kamitakahara et al [ 66 ] reported that the wide contact surface area is an important factor for cell proliferation and cells could proliferate easily.…”
Section: Resultsmentioning
confidence: 99%
“…CS/HA-based biomaterials have been extensively applied for bone substitutes, tissue engineering scaffolds and bone cement [ 14 , 15 , 16 ]. Different approaches have been established to make a ceramic or polymeric based coatings on the surface of metals or alloys [ 17 , 18 , 19 , 20 ]. It was reported that Ti6Al4V substrate was modified by a chitosan film to promote the nucleation of HA/Ag composite coatings deposited by the thermal substrate method [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the inorganic binders without the VOC are completely environmentally friendly and have become a hot spot for coating research. They mainly include phosphate [18,19], silica sol [20,21] and silicate coatings [22,23]. Silica sol paints form a film by polymerization of silanol group but cohesion is larger during polycondensation, which is likely to cause the coatings to crack or even cause large-areas to fall off.…”
Section: Introductionmentioning
confidence: 99%
“…Waterborne inorganic paints are promising substitutes. Waterborne inorganic anticorrosion paints mainly include silicate [11,12], silica sol [13,14], and phosphate paints [15,16]. Silicate and silica sol improve adhesion between metal and coating [17].…”
Section: Introductionmentioning
confidence: 99%